The correct name for the subfamily containing Kalanchoe is Crassulaceae subfam. Cotyledonoideae, and not Crassulaceae subfam. Kalanchooideae, with amendment of the circumscription of Crassulaceae subfam. Cotyledonoideae - Smith, Gideon F.; Monro, Anna M. (Phytotaxa, 2024)
In 2022, a proposal to reject the subfamily name Crassulaceae subfam. Cotyledonoideae was submitted, through publication, as is required in the currently operative International Code of Nomenclature for algae, fungi, and plants, to the General Committee (GC), and through that body, automatically to the (Permanent) Nomenclature Committee for Vascular Plants (NCVP). Drafting and publication of the rejection proposal was undertaken because, despite having priority, the name Crassulaceae subfam. Cotyledonoideae, has not been used in the taxonomic literature relating to the family for the past 30 years. Rather, virtually all the published studies on the Crassulaceae that referenced subfamilies used Crassulaceae subfam. Kalanchooideae, for which the informal name “Kalanchoe clade” has been used exclusively in phylogenetic studies of the Crassulaceae. However, the NCVP (in February 2024) recommended against the proposal to reject the name Crassulaceae subfam. Cotyledonoideae. This recommendation was submitted to the GC, which supported the NCVP and rejected the rejection proposal (in July 2024), despite an appeal against this outcome having been lodged (in February 2024). The further procedural treatment of the report of the GC is discussed in this paper. The outcome of the proposal having been rejected is that the subfamily name Crassulaceae subfam. Cotyledonoideae must be adopted in the stead of the subfamily name Crassulaceae subfam. Kalanchooideae for a group of four predominantly, but not exclusively, southern African genera, i.e., Adromischus, Cotyledon, Kalanchoe, and Tylecodon. Kalanchoe in particular has a wider natural geographical distribution range. Since the original circumscription of Crassulaceae subfam. Cotyledonoideae included a disparate group of six southern and northern hemisphere genera, a further outcome of the proposal having been rejected is that the circumscription of this subfamily must be amended. This is done here.